1999
DOI: 10.1115/1.2836718
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vane-Blade Spacing on Transonic Turbine Stage Aerodynamics: Part I—Time-Averaged Data and Analysis

Abstract: A comprehensive study has been performed to determine the influence of vane-blade spacing on transonic turbine stage aerodynamics. In Part I of this paper, an investigation of the effect of turbine vane–blade interaction on the time-mean airfoil surface pressures and overall stage performance parameters is presented. Experimental data for an instrumented turbine stage are compared to two- and three-dimensional results from four different time-accurate Navier–Stokes solvers. Unsteady pressure data were taken fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…According to the open literature, this trend is confirmed by some authors [42][43][44][45][46] but seems not general (as also reported and discussed by [41]), either for a lack of detailed data or for a case dependency in the stator wake-potential field coupling along the axial direction, in the axial gap region.…”
Section: Axial Gapmentioning
confidence: 72%
“…According to the open literature, this trend is confirmed by some authors [42][43][44][45][46] but seems not general (as also reported and discussed by [41]), either for a lack of detailed data or for a case dependency in the stator wake-potential field coupling along the axial direction, in the axial gap region.…”
Section: Axial Gapmentioning
confidence: 72%
“…9 1.31 0.45 Meas. Venable et al 10 4.84 1.10 URANS Chang and Tavoularis 19 -1.18 URANS Yamada et al 24 3.99 0.18 Meas. Gaetani et al 25 2.30 0.55 Meas.…”
Section: Analysed Data and Linear Correlation Methodsmentioning
confidence: 99%
“…Funazaki et al 3 -6.24 1.00 3 Restemeier et al 9 -1.39 0.89 3 Venable et al 10 2.00 0.66 3 Chang and Tavoularis 19 0.35 0.01 3 Yamada et al 24 -2.89 0.74 3 Gaetani et al 25 -0.33 0.01 3 TFD -1.71 0.99 3 loss mechanism. The study by Perdichizzi 17 suggested that the spanwise position of the two-dimensional flow is influenced by the Mach number, which indicates that the influence on the interaction exists.…”
Section: Correlations Of Stator Outlet Mach Number and Reduced Blade mentioning
confidence: 99%
“…Studies have been made to investigate the effect of axial gap on the aerodynamic performance of the turbine stage, and some efforts among them revealed the importance of unsteadiness and the mechanism of the losses in turbomachinery. Venable et al [2] varied the vane-blade spacing in a transonic turbine and reported the tendency of adiabatic efficiency increase when the rotorstator axial gap is increased. He [3] made three-dimensional unsteady Navier Stokes analysis of stator-rotor interaction and established the same result.…”
Section: Introductionmentioning
confidence: 99%